Bercerita dengan Boneka Kertas dapat Meningkatkan Kemandirian Anak Usia Pra Sekolah - Suryaningsih, Chatarina; Pawesti, Galuh Dyah Arum; Imelisa, Rahmi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Pre-school children entered developments stage that include gross motor development, fine motor,socialization, independence, speech and language. Each stage of development has the potential fordevelopment disruption, including the development of independence. Factors that can influenceindependence are genes, parents, appreciation, criticism, and stimulation. Stimulation can be done withplaying telling story. This study aim to determine the effect of storytelling using paper dolls on theindenpendence of pre-school aged at TK Purnama Cimahi Year 2018. The research design used was quasiexperiment eith one group pretest-posttes approach. The population of this study were pre-school agechildern with a sample of 22 childern from 36 months to 72 months old. Samples were taken with totalsampling. Data analysis using Willcoxon Test. Data colletion used observation sheet measure pretest posttest.The data results of data analysis showed that the average growth of the pretest was 7,05 while the avarageposttest was 9.27result of bivariate analysis is p value 0,001 In conclusion, there is evidence of the effect ofstorytelling using paper dolls on the independence of pre-school aged at TK Purnama Cimahi Year 2018. It isrecommended for TK Purnama to make storytelling using paper doll as one of the stimulate to increase theindependence of preshoolers.